Model Dinamika Ketersedian Pangan - Studi Kasus : Ketersediaan Beras di Wilayah Madiun, Jawa Timur - Tri Purwadi; Lilik Sutiarso; Putu Sudira (agriTECH, 2003)
In order to predict and determine level of food security in a certain area, a dynamic system approach model of food supply-demand planning that based on regional resources was developed. The model was run using both primary and secondary data, which were gathered in the study area, Madiun Region, East Java Province. One of food crop comodities that was focused for simulating the model was rice. To validate the developed model, one scenario was selected, there were no changing of planting or harvesting area and rice productivity level, also rice imported from other areas (countries) was zero for five next years. The simulation results indicated that the level of actual food security (1.29 - 1.27 years) was higher than government's level (1.25 years), though the rice market price decreased gradually.